Transport Characteristics of Tryptanthrin and its Inhibitory Effect on P-gp and MRP2 in Caco-2 Cells - Xingang Zhu; Xuelian Zhang; Guo Ma; Junkai Yan; Honghai Wang; Qing Yang (Frontiers Media S.A., 2011)
Purpose. Tryptanthrin, an indole quinazoline alkaloid with multiple medical activities, has been recently under preclinical development as an anti-tuberculosis and anti-tumor drug. The aims of this study are to characterize the intestinal transport of tryptanthrin in Caco-2 cells, to determine whether P-glycoprotein (P-gp) and multidrug resistance-associated protein 2 (MRP2) are involved in this issue, and to evaluate the potential influence of tryptanthrin on the function of P-gp and MRP2. Methods. Transport assays of tryptanthrin were performed in Caco-2 monolayers with or without the supplement of P-gp and MRP2 inhibitors. Transport assays of P-gp and MRP2 substrates were also performed in the presence of tryptanthrin. The effect of tryptanthrin on the expression of P-gp and MRP2 was analyzed by reverse transcriptase-PCR. Results. Both absorption and secretion of tryptanthrin were concentration-independent at a low concentration range of 0.8-20 µM. The apparent permeability (Papp) for the apical (AP) to basolateral (BL) was 6.138 ± 0.291 × 10-5. The ratio of Papp (BL→AP) to Papp (AP→BL) was 0.77, suggesting greater permeability in the absorptive direction. Both the P-gp inhibitor, verapamil, and the MRP2 inhibitor, glibenclamide, didn't affect the efflux transport of tryptanthrin. The efflux transport of the P-gp substrate, digoxin, and the MRP2 substrate, pravastatin sodium, decreased when tryptanthrin was present. However, tryptanthrin didn't change the expression of P-gp and MRP2. Conclusions. Tryptanthrin was well absorbed across the Caco-2 monolayers, and its transepithelial transports were dominated by passive diffusion. Tryptanthrin was not a substrate, but a potential inhibitor of P-gp and MRP2. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.